2018
DOI: 10.1016/j.csbj.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analysis Reveals Conservation of Intrinsic Disorder in the Linker Sequences of Prokaryotic Dual-family Immunophilin Chaperones

Abstract: The two classical immunophilin families, found essentially in all living cells, are: cyclophilin (CYN) and FK506-binding protein (FKBP). We previously reported a novel class of immunophilins that are natural chimera of these two, which we named dual-family immunophilin (DFI). The DFIs were found in either of two conformations: CYN-linker-FKBP (CFBP) or FKBP-3TPR-CYN (FCBP). While the 3TPR domain can serve as a flexible linker between the FKBP and CYN modules in the FCBP-type DFI, the linker sequences in the CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Bioinformatic analysis showed that all CFBP linkers, in spite of their sequence dissimilarity, possess intrinsic disorder (ID), a hallmark of flexible protein linkers [16], as shown later with Flavobacterium johnsoniae CFBP (Figure 3). Thus, both classes of DFPPIs contain flexible linkers, serving as connector between the two classical PPI/immunophilin domains, which offered the first indication that the two domains may function as independent functional modules, able to freely bend against each other [14,16].…”
Section: Dfppi Structurementioning
confidence: 77%
See 4 more Smart Citations
“…Bioinformatic analysis showed that all CFBP linkers, in spite of their sequence dissimilarity, possess intrinsic disorder (ID), a hallmark of flexible protein linkers [16], as shown later with Flavobacterium johnsoniae CFBP (Figure 3). Thus, both classes of DFPPIs contain flexible linkers, serving as connector between the two classical PPI/immunophilin domains, which offered the first indication that the two domains may function as independent functional modules, able to freely bend against each other [14,16].…”
Section: Dfppi Structurementioning
confidence: 77%
“…In analogy to the single family PPIases, it is safe to assume that the DFPPIs play a major role to facilitate folding of their client proteins, which also remain unidentified. Expanding on our previous suggestions [13,14,16], I propose a model (Figure 4), in which the bifunctional DFPPI is located, perhaps together with translating polyribosomes (polysomes), at specialized cellular sites that is tentatively named "translational co-folding centers" or TCCs.…”
Section: Physiological Function Of Dfppismentioning
confidence: 93%
See 3 more Smart Citations